PENGEMBANGAN MODIFIKASI PERMAINAN TRADISIONAL TERINTEGRASI AL-ISLAM UNTUK MENINGKATKAN AFEKTIF PESERTA DIDIK KELAS TINGGI SD IT AL-FALAH KOTA SUKABUMI - Rayi Santika Ma’ruf; Bachtiar Bachtiar; Wening Nugraheni (Indonesia Sport Journal, 2019)
Research Objectives (1) Reintroduce traditional games that have been forgotten because of the times; (2) Modification of the traditional game that integrates al-Islam to improve the affective of high-class students of Al-Falah Elementary School of Islamic Union, Sukabumi City. This study refers to the development model of Sugiyono, as follows (1) potential and problems; (2) data collection; (3) product design; (4) design validation; (5) product revisions; (6) product testing; (7) product revisions; (8) trial use; (9) final product. The subjects of this study were students of high school Al-Falah Elementary School Islamic Association of Sukabumi City. The data collection technique used by researchers is descriptive percentage. While the data in the form of suggestions and reasons for choosing answers were analyzed using qualitative analysis techniques. From the results of this development research, the average percentage of small group trials was 78.25% with the Very Good criteria, and the results of the percentage of large-scale trials were 83% with Very Good criteria.